Tafsir Al-Qur’an Ibnu Arabi: Telaah Atas Beberapa Ayat Penafsiran Al-Qur’an Sebagai Penguat Ajaran Wahdat al-Wujûd - Basrian Basrian; Muhammad Noor 'Ashry; Muhammad Akbar Ramadhani (Jurnal Ilmiah Ilmu Ushuluddin, 2026)
This article scrutinized Ibn Arabi's interpretations of several Qur'anic verses, particularly his efforts to bolster the doctrine of Wahdat al-Wujûd. As a leading Sufi thinker, his interpretations often stirred controversy due to their departure from literal meanings. This qualitative study examined Ibn Arabi's works (Al-Futuhat al-Makkiyyah, Fushush al-Hikam) and the diverse views of scholars on his exegesis. The findings revealed that Ibn Arabi's exegesis was a shufi nazhari interpretation, seeking to align the Qur'anic text with the Wahdat al-Wujûd concept. This approach frequently contradicts literal (zahir) interpretations and Arabic linguistic norms, sparking heated debate among scholars. While some scholars were receptive to his views, the majority vehemently rejected them as deviant. The significance of his exegesis lies in its unconventional yet sincere attempt to integrate spiritual experience with textual understanding.